Binding of an inert, cationic osmium probe to walls of Bacillus subtilis. - Beveridge, T J (1982)
X-ray fluorescence spectroscopy and electron microscopy of unstained specimens have been used to study the binding of chloropentaammineosmium(III) chloride to isolated walls of Bacillus subtilis. Native walls bound 0.220 mumol of the osmium probe per mg (dry weight) of walls, whereas walls which were chemically treated to neutralize the available carboxylate groups of the peptidoglycan bound only 0.040 mumol. Teichoic acid-depleted walls bound 0.210 mumol. Thin sections of all wall types showed the osmium probe to be scattered throughout the wall matrix as a small staining deposit. The results support the idea that the metal ion-binding capacity of these walls is mediated by the available carboxylate groups in the wall fabric.